Media Permainan Kartu Kuartet Dalam Meningkatkan Hasil Belajar Geometri Siswa Sekolah Dasar - Andi Ardhila Wahyudi; Hamdana Hadaming (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2023)
The purpose of this study was to improve the learning outcomes of Geometry grade IV students at SD Bawakaraeng 1 with the application of quartet game media. Using the Descriptive Analysis method of classroom action research, namely studies used to collect, process, analyze, interpret and conclude data so that a systematic picture is obtained in increasing activity and learning outcomes. The subjects in this study were all 24 students of grade IV. The instruments used were test sheets and student activity observation sheets. Data collection techniques are tests and observations. There was a significant increase after applying the quartet game media in learning geometry. The average percentage of positive activity was in the good category, namely 73.95%, while in cycle 2 it was in the very good category, namely 85.39%. For the percentage of negative activity in cycle 1 of 12.5% ​​and cycle 2 of 4.1%, this means that positive activity has increased and negative activity has decreased. And there was an increase in the number of students who had completed or reached KKM, namely as many as 11 students or 45.83% in cycle 1 and as many as 21 students who completed or 87.5% in cycle 2. There was an increase in student learning outcomes from cycle 1 to cycle 2 percentage of 41.67%. This shows that the application of quartet game media on geometry material can improve students' mathematics learning outcomes at SD Bawakaraeng 1 Makassar city.